A New Look at Transgenerational Trauma Transmission: Second‐Generation Latino Immigrant Youth. Issue 3 (July 2014) - Phipps, Ricardo M.; Degges‐White, Suzanne
<x xml:space="preserve">Abstract</x> Transgenerational trauma, which was first documented in the 1960s to describe trauma symptoms experienced by descendants of holocaust survivors, has been linked to psychological and physiological transmission factors. Although traumatization still occurs among contemporary immigrant groups, particularly Latino immigrants, little attention has been paid to the experiences of these individuals. The authors present the relevant cultural considerations and conditions that support the need for proactive assessment of transgenerational trauma in U.S.‐born Latino youth. El trauma transgeneracional, que fue documentado por primera vez en los años 60 para describir los síntomas de trauma experimentados por descendientes de los supervivientes del holocausto, ha sido relacionado con factores de transmisión psicológicos y fisiológicos. Aunque la traumatización todavía ocurre entre grupos de inmigrantes en la actualidad, particularmente en inmigrantes latinos, se ha prestado escasa atención a las experiencias de estos individuos. Los autores presentan las consideraciones y condiciones culturales relevantes que apoyan la necesidad de realizar una evaluación proactiva del trauma transgeneracional en la población de jóvenes latinos nacidos en los Estados Unidos.